PENERAPAN MICROSITE PADA MATERI STATUS, PERAN SOSIAL, DIFERENSIASI DAN STRATIFIKASI SOSIAL UNTUK MENINGKATKAN LITERASI DIGITAL SERTA LITERASI BUDAYA DAN KEWARGANEGARAAN - Alfina, Dinazat Gita; Adhi Suciptaningsih, Oktaviani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Teachers play a role in managing learning activities, so that teaching and learning activities can run well and improve students' abilities to achieve the learning goals that must be achieved. The use of media in the learning process will help smoothness, effectiveness and efficiency to achieve goals. This research aims to analyze the application of the s.id microsite on material about status, social roles, differentiation and social stratification to increase digital literacy as well as cultural and civic literacy. This research uses a Classroom Action Research (PTK) design with a quantitative approach. This research consists of two cycles, each cycle consisting of planning, action, observation and reflection activities. The research subjects were 27 students in class VII A of SMP Negeri 1 Malang. In the pre-cycle data, it was found that 17 students had completed their studies with a percentage of 63% of the total 27 students. Then in cycle I there was an increase to 19 students with a percentage of 70%, then there was an increase in cycle II to 21 students who completed it with a percentage of 78% in accordance with KKM 70. It can be concluded that the application of microsite s.id on status material, social roles, differentiation and social stratification can improve student learning outcomes as well as increase digital literacy and civic cultural literacy, seen from skills in using technology and respect and respect for differences.